How deep is China's environmental Kuznets curve? An analysis based on ecological restoration under the Grain for Green program. (January 2018) - Zhang, Junze; Luo, Mengting; Cao, Shixiong
Highlights: The environmental Kuznets curve's minimum income was between 20 200 and 27, 000 RMB. The curve's inflection point changed in response to various factors. Residents environmental attitudes shaped the environmental Kuznets curve. Our methods provide a sustainable development tool for developing countries. Abstract: Environmental Kuznets curve theory predicts that rapid economic development will initially and unavoidably create environmental problems until these problems are solved at higher development levels. However, because different economies face different impacts from economic growth, some may find ways to shorten the environmental Kuznets curve. To understand the characteristics of a "Kuznets curve" based on Chinese environmental attitudes and the factors that influence these attitudes, we interviewed 3000 randomly selected Chinese adults in 2014 using stratified random sampling in six areas (four provinces and two provincial-scale municipalities) that had been affected by the national Grain for Green program. Our goal was to determine their opinions on China's environmental policy. Based on their responses, we calculated that the minimum value of the environmental Kuznets curve (the income at which priorities change from income to environmental protection) occurred at a per capita income of between 20 200 and 27, 000 RMB (an increase of 61.6% compared with results from a similar survey in 2004). We found significant impacts of income, education level, age, gender, employment, and region on Chinese environmental choices. To achieve sustainable socioeconomic development, China's government must account for how these factors affect public responses to its policy initiatives. China's government must also find ways to increase personal income faster to speed China's progress along the environmental Kuznets curve.